Malondialdehyde and 3-Nitrotyrosine in Exhaled Breath Condensate in Retired Elderly Coal Miners with Chronic Obstructive Pulmonary Disease - Jong Seong Lee; Jae Hoon Shin; Ju-Hwan Hwang; Jin Ee Baek; Byung-Soon Choi (Elsevier, 2014)
Background: Chronic obstructive pulmonary disease (COPD) is an important cause of occupational mortality in miners exposed to coal mine dust. Although the inflammatory mediators involved in COPD have not been defined, many studies have shown that inflammatory mediators such as reactive oxygen and nitrogen species are involved in orchestrating the complex inflammatory process in COPD. Methods: To investigate the relevance of exhaled biomarkers of oxidative and nitrosative stress in participants with COPD, we determined the levels of hydrogen peroxide, malondialdehyde (MDA), and 3-nitrotyrosine (3-NT) in exhaled breath condensate (EBC) in 90 retired elderly coal miners (53 non-COPD and 37 COPD participants). Results: Mean levels of MDA (4.64 nM vs. 6.46 nM, p = 0.005) and 3-NT (3.51 nM vs. 5.50 nM, p = 0.039) in EBC were significantly higher in participants with COPD. The median level of MDA did show statistical difference among the COPD severities (p = 0.017), and the area under the receiver operating characteristic curve for MDA (0.67) for the diagnostic discrimination of COPD indicated the biomarker. The optimal cutoff values were 5.34 nM (64.9% sensitivity and 64.2% specificity) and 5.58 nM (62.2% sensitivity and 62.3% specificity) for MDA and 3-NT, respectively. The results suggest that high levels of MDA and 3-NT in EBC are associated with COPD in retired elderly miners. Conclusion: These results showed that the elevated levels of EBC MDA and EBC 3-NT in individuals with COPD are biomarkers of oxidative or nitrosative stress.